The role and importance of celebrities in achieving customer satisfaction and loyalty - Pavlović, Sanjica (Array, 2020)
The aim of this research is to gain a better insight into customer satisfaction and loyalty as a result of celebrity brand endorsements, based on the data collected through primary and secondary research. The paper explores the concept of brand, as well as consumer attitudes towards brands and the use of celebrities in advertising. A brand is a name, symbol or design that identifies a product or service that is commonly associated with quality. In today’s market, celebrities are a vital element of brand advertising and a major factor in driving product sales. New media advertising has become essential for successful communication with the contemporary consumer.